New product development and firm value in mobile handset production - Heli Koski; Tobias Kretschmer (The Research Institute of the Finnish Economy (ETLA), 2009)
We study the effect of new product introduction on firm value. Using a unique sample on mobile phone handset introduction by 16 major handset manufacturers over 10 years, we distinguish between imitative product introduction and truly innovative product introduction. We find that while most product introduction is imitative, both types of innovation increase firm value. However, truly innovative innovation is found to increase firm value by more than imitative introductions.
Keywords: 330; Product innovation; mobile telephony; firm value; Innovationsmanagement; Geschäftswert; Immaterielles Anlagevermögen; Mobiltelefon; Welt